2021
DOI: 10.2147/cmar.s278087
|View full text |Cite
|
Sign up to set email alerts
|

Improving Social Support to Increase QoL in Lung Cancer Patients

Abstract: Lung cancer is the most common cause of cancer deaths in the world. According to the World Health Organization, over 2 million new lung cancer cases were reported worldwide in 2018, and there were 1.76 million deaths from the disease. Due to its non-specific symptoms, the disease is usually detected at an advanced stage, which gives few treatment options and a short survival rate after diagnosis. That is why improving QoL in the last months of a patient’s life is enormously important. The purpose of this study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 40 publications
3
28
0
Order By: Relevance
“…Previous studies have also demonstrated that supportive therapy can benefit patients with lung cancer,27 as well as ovarian cancer, breast cancer, prostate cancer, etc 28. In patients with lung cancer, improved social support is beneficial in improving emotions and the quality of life 29. Therefore, our findings confirmed the significance of supportive therapy as part of a comprehensive biopsychological treatments.…”
Section: Discussionsupporting
confidence: 84%
“…Previous studies have also demonstrated that supportive therapy can benefit patients with lung cancer,27 as well as ovarian cancer, breast cancer, prostate cancer, etc 28. In patients with lung cancer, improved social support is beneficial in improving emotions and the quality of life 29. Therefore, our findings confirmed the significance of supportive therapy as part of a comprehensive biopsychological treatments.…”
Section: Discussionsupporting
confidence: 84%
“…Perceived social support is a subjective perception and assessment of the degree of support received from one’s external surroundings, such as family, friends, and significant others ( Zimet et al, 1990 ). It allows for solving problems or regulating emotions arising from stressful events by providing tangible assistance (such as medical assistance, financial support, and useful information) or emotional values (such as empathy and belonging; Mo et al, 2020 ; Hofman et al, 2021 ). The perceived social support of healthcare professionals in township health centers during the COVID-19 pandemic was at a moderate level, with a score of 49.10, and perceived social support positively affected individual resilience, further explaining previous studies that found social support to be an important resource for healthcare professionals improving their ability to cope with stress during the COVID-19 pandemic ( Aughterson et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Social support is defined as an individual's access through social ties to other individuals, groups, and the larger community, which is a social interaction process related to altruism, sense of obligation, and reciprocity (Lin et al, 1979;Hofman et al, 2021). According to coping theory, social support is one of the main coping strategies of individuals facing stress, and reduces the possible negative effects of stressful events by solving problems (i.e., problems are solved by getting information and practical help from social ties) and easing emotions (i.e., regulating negative emotional responses through social ties) (Lazarus, 1993;Mo et al, 2020).…”
Section: Introductionmentioning
confidence: 99%